The show choir handbook - Alder, Alan L., 1973- (Rowman and Littlefield, 2016)
The Show Choir Handbook is a resource for current and future music educators who administer show choirs. With most literature on the topic either out of date or focused on the teaching techniques limited to vocal jazz (drawing on the choral genre's origins as "swing choirs"), instructors are in dire need of a resource that addresses music produced by publishers and choral arrangers.